Pengaruh Lingkungan Kerja dan Gaya Kepemimpinant terhadap Komitmen Organisasi melalui Motivasi Kerja sebagai Variabel Intervening pada Karyawan Bagian Produksi PT. Handal Sukses Karya Jepara - Budianto, Achmad; Indaryani, Mamik; Suroso, Iwan (Jurnal Studi Manajemen Bisnis, 2024)
This research aims to analyse the influence of the work environment and leadership style on work motivation and organizational commitment as well as analysing the influence of work motivation on organizational commitment at PT. Reliable Success by Jepara. This research design uses descriptive and quantitative analysis methods. The population used in this research is all employees of PT. Reliable Success Karya Jepara as many as 224 people. Based on the established criteria, 142 respondents were used as samples in this study. The results of this research are as follows: 1) The work environment has a positive and significant effect on the work motivation of PT employees. Reliable Success by Jepara. 2) Leadership style has a positive and significant effect on the work motivation of PT employees. 3) The work environment has a positive and significant effect on the organizational commitment of PT. Handal Sukses Karya Jepara. 4) Leadership style has no significant effect on organizational commitment. 5) Work motivation has a positive and significant effect on organizational commitment.